The Forward Premium Puzzle Revisited - Meredith, Guy (IMF Working Papers; Working Paper ;, 2002)
The forward premium is a notoriously poor predictor of exchange rate movements. This failure must reflect deviations from risk neutrality and/or rational expectations. In addition, a mechanism is needed that generates the appropriate correlation between the forward premium and shocks arising from risk premia or expectations errors. This paper extends McCallum (1994) to show how such a correlation can arise from the response of monetary policy to output and inflation, which are in turn affected by the exchange rate. The theoretical models considered all generate results that are consistent with the forward premium being a biased predictor of short-term exchange rate movements; the bias decreases, however, as the horizon of the exchange rate change lengthens. Another common feature of the models is that the true reduced-form equation for exchange rate changes contains variables other than the interest differential, providing a justification for "eclectic" relationships for forecasting exchange rates. The results, however, remain consistent with using uncovered interest parity as a building block for structural models.